Comparative efficacy and safety of prophylactic norepinephrine and phenylephrine in spinal anesthesia for cesarean section: A systematic review and meta-analysis with trial sequential analysis - Liu, Peng; He, Hong; Zhang, Shan-Shan; Liang, Yun; Gao, Zi-Jun; Yuan, Hui; Dong, Bu-Huai (Frontiers in Pharmacology, 2022)
Background: Phenylephrine is the first-line drug used to maintain blood pressure in cesarean delivery, but it is highly likely to cause bradycardia and depress cardiac activity in pregnant women; in recent years norepinephrine has been considered as its alternative and it is thought that prophylactic use of vasopressors may reduce the incidence of hypotension after spinal anesthesia, based on this, our study compared the efficacy of both. Methods:We searched CNKI, PubMed, Embase, Web of science, clinicaltrials.gov,Medline and Cochrane Library for randomized controlled trials on elective cesarean delivery under spinal anesthesia to compare the efficacy of prophylactic use of norepinephrine and phenylephrine. The search period was from the build to July 2022, and the primary outcome indicator was the incidence of bradycardia. Statistical analysis using Rev manager 5.4, Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) was used to evaluate the quality of evidence for each main finding. Results: A total of 12 papers were included in the analysis. The incidence of bradycardia (RR=0.20,95%CI:0.28 to 0.49,P<0.00001)and reactive hypertension(RR=0.58,95%CI 0.40 to 0.83,P=0.003) were significantly lower in the norepinephrine group (NE) compared with the phenylephrine group (PE), and the differences were statistically significant; in contrast, there were no statistical differences in hypotension, nausea, vomiting, and umbilical cord blood gas analysis values pH[hypotension:RR=1.29,95%CI 0.93 to 1.79,nausea:RR=0.79,95%CI 0.60 to 1.06,P=0.11,vomiting:RR=0.69,95%CI 0.37 to 1.27,P=0.23,arterial:MD=0.00,95%CI -0.00 to 0.01,P=0.22,vein :MD=0.01,95%CI -0.00 to 0.02,P=0.06]. Conclusion: Prophylactic use of norepinephrine is safe and effective in maintaining maternal hemodynamics without causing adverse events to the pregnant woman or fetus.